2004
DOI: 10.1016/j.jorganchem.2004.05.040
|View full text |Cite
|
Sign up to set email alerts
|

Open shell organometallics: a general analysis of their electronic structure and reactivity

Abstract: Transition metal organometallic compounds that contain fewer than 18-electrons and two or more unpaired electrons are generally excluded from treatises of either Werner-type coordination compounds or organometallic chemistry. However, they can be seen as the bridge filling the gap between these two traditional areas of coordination chemistry. Their magnetic and optical properties are reminiscent of the Werner-type complexes, whereas their chemical reactivity parallels that of the lower-valent organometallics. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
64
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 87 publications
(66 citation statements)
references
References 65 publications
0
64
0
2
Order By: Relevance
“…[16] The steric bulk of the PMe 3 and 1,2,4-C 5 H 2 tBu 3 ligands, in combination with the electron-pairing stabilization provided by the spin-quartet state, [42,43] accounts for the absence of solvent coordination to complex 5 a. The oxidatively induced reductive elimination of compounds containing two one-electron ligands ([M(X)(Y)], leading to the elimination of X À Y) has previously been demonstrated for dialkyl complexes [M(R) 2 ] to give the alkane coupling product R À R [18,[44][45][46][47][48][49][50] and for alkyl-hydride complexes [M(R)(H)] to give the corresponding alkane RÀH, [18,47] plus products originating from [M] + .…”
Section: Electron Solvent Adduct [Mocp*a C H T U N G T R E N N U N G mentioning
confidence: 99%
“…[16] The steric bulk of the PMe 3 and 1,2,4-C 5 H 2 tBu 3 ligands, in combination with the electron-pairing stabilization provided by the spin-quartet state, [42,43] accounts for the absence of solvent coordination to complex 5 a. The oxidatively induced reductive elimination of compounds containing two one-electron ligands ([M(X)(Y)], leading to the elimination of X À Y) has previously been demonstrated for dialkyl complexes [M(R) 2 ] to give the alkane coupling product R À R [18,[44][45][46][47][48][49][50] and for alkyl-hydride complexes [M(R)(H)] to give the corresponding alkane RÀH, [18,47] plus products originating from [M] + .…”
Section: Electron Solvent Adduct [Mocp*a C H T U N G T R E N N U N G mentioning
confidence: 99%
“…The addition of this data set is prompted by the increasing attention being paid by many workers to the relative energies of spin states of transition metal systems because of the importance of spin states for structures, properties, and chemical reactivities of organometallic complexes and for functional nanotechnology. [52][53][54][55][56][57][58][59][60][61][62] Holthausen made a systematic study 63 of the ability of density functionals to predict 3d-4s excitation energies in transition metal cations and found that some functionals, even though performing well for main group atomization energies, show large errors for transition metal atomic excitation energies. Because we seek a functional that is accurate for both main-group and transition metal chemistry, our small database has both types of atoms.…”
Section: Introductionmentioning
confidence: 99%
“…[15] Ein Wechsel des Spinzustandes zwischen den Oxidationsstufen ist jedoch durchaus möglich und könnte sogar zu einem beschleunigten Reaktionsschritt führen, wenn ein Spinwechsel ausreichend schnell verläuft. [16] Theoretische Studien von solchen spinverbotenen Reaktionen sind viel aufwändiger. In den letzten Jahren wurden erhebliche Fortschritte in diesem Zusammenhang gemacht, aber bisher noch nicht auf Reaktionsschritte in Schema 1 ausgeweitet.…”
unclassified